2004
DOI: 10.1021/jf0305938
|View full text |Cite
|
Sign up to set email alerts
|

8S Globulin of Mungbean [Vigna radiata (L.) Wilczek]:  Cloning and Characterization of Its cDNA Isoforms, Expression in Escherichia coli, Purification, and Crystallization of the Major Recombinant 8S Isoform

Abstract: Three isoforms of the cDNA of the major 8S globulin of mungbean, 8Salpha, 8Salpha', and 8Sbeta, were isolated, cloned, and characterized. The cDNA sequences of 8Salpha, 8Salpha', and 8Sbeta had open reading frames of 1362, 1359 or 1362, and 1359 bp, respectively, which code for 454, 453 or 454, and 453 amino acids corresponding to molecular weights of 51 973, 51 627 or 51 758, and 51 779, respectively. Homology in terms of cDNA and amino acid sequences was 91-92% between 8Salpha and 8Salpha', 87% between 8Salp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 30 publications
4
50
0
Order By: Relevance
“…1) were replaced with cysteine residues by the use of a QuickChange site-directed mutagenesis kit (Stratagene, U.S.A.) and mutation sites were confirmed by DNA sequencing. The plasmid pET-21d-8Sα globulin, which is the expression vector for WT (Bernardo et al, 2004), was used as a template. The primers used were for F59C (Phe59→ Cys59): 5′CCGTGTTGTTAGAGTGCATGTCCAAACCC3′ and 5′ GGGTTTGGACATTGCACTCTACAACACGG3′; for I99C (Ile99 → Cys99): 5′GGCAGAGACTCCACCTGCCTTGAGCAAGGCCATG3′ and 5′CATGGCCT TGCTCAAGGCAGTTGGAGTCTCTGCC3′; for A213C (Ala213→ Cys213): 5′GGGAATTGACCAAACATTGCAAATCTAGTTCAAAG3′ and 5′CTTTGAAC-TAGATTTGCAATGTTTGGTCAATTCCC3′ (mutations are indicated by underlined letters).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
See 3 more Smart Citations
“…1) were replaced with cysteine residues by the use of a QuickChange site-directed mutagenesis kit (Stratagene, U.S.A.) and mutation sites were confirmed by DNA sequencing. The plasmid pET-21d-8Sα globulin, which is the expression vector for WT (Bernardo et al, 2004), was used as a template. The primers used were for F59C (Phe59→ Cys59): 5′CCGTGTTGTTAGAGTGCATGTCCAAACCC3′ and 5′ GGGTTTGGACATTGCACTCTACAACACGG3′; for I99C (Ile99 → Cys99): 5′GGCAGAGACTCCACCTGCCTTGAGCAAGGCCATG3′ and 5′CATGGCCT TGCTCAAGGCAGTTGGAGTCTCTGCC3′; for A213C (Ala213→ Cys213): 5′GGGAATTGACCAAACATTGCAAATCTAGTTCAAAG3′ and 5′CTTTGAAC-TAGATTTGCAATGTTTGGTCAATTCCC3′ (mutations are indicated by underlined letters).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…In designing the mutation, we used the soybean proglycinin structure as basis since the amino acid sequences of proglycinin A1aB1b and 8Sα globulin had 68% identity which is the highest among other 7S, 8S globulins (Bernardo et al, 2004;Itoh et al, 2006). Earlier work has shown that the soybean proglycinin A1aB1b mutant proteins with new cysteine residues and disulfide bonds (intraprotomer or interprotomer) were improved in their heat-induced gel-forming ability and were more stable than the wild type against thermal denaturation and with greater resistance against chymotrypsin digestion .…”
Section: Designing the Sulfhydryl Groups And Disulfide Bondmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, in V. luteola, all of the sulfur is contributed by methionine; there are no cysteine residues. Predicted proteins of vicilins of V. angularis (Fukuda et al 2007), V. radiata (Bernardo et al 2004), and V. unguiculata (GenBank AM905848) also contain no cysteine, and neither does the Ph. vulgaris vicilin.…”
Section: Amino Acid Composition Of V Luteola Vicilins Compared With mentioning
confidence: 99%